Magnetic nanoparticle hyperthermia potentiates paclitaxel activity in sensitive and resistant breast cancer cells - Rivera-Rodriguez A (Dove Medical Press, 2018)
Angelie Rivera-Rodriguez,1 Andreina Chiu-Lam,2 Viacheslav M Morozov,3,4 Alexander M Ishov,3,4 Carlos Rinaldi1,2,4 1J. Crayton Pruitt Family Department of Biomedical Engineering, University of Florida, Gainesville, FL, USA; 2Department of Chemical Engineering, University of Florida, Gainesville, FL, USA; 3Department of Anatomy and Cell Biology, University of Florida College of Medicine, Gainesville, FL, USA; 4UF Health Cancer Center Gainesville, FL, USA Introduction: Overcoming resistance to antimitotic drugs, such as paclitaxel (PTX), would represent a major advance in breast cancer treatment. PTX induces mitotic block and sensitive cells exit mitosis dying by mitotic catastrophe. Resistant cells remain in block and continue proliferation after drug decay, denoting one of the PTX resistance mechanisms. Mild hyperthermia (HT) triggers mitotic exit of PTX-pretreated cells, overcoming PTX resistance and suggesting HT-forced mitotic exit as a promising strategy to potentiate PTX. Methods and results: Superparamagnetic iron oxide nanoparticles (SPIONs) were used to deliver mild HT at 42°C in PTX-pretreated breast adenocarcinoma MCF-7 cells sensitive and resistant to PTX. To evaluate mechanism of cell death, cells were classified based on nuclear morphology into interphase, mitotic, micronucleated, and apoptotic. The combined PTX→SPION treatment resulted in an increase in the percentage of micronucleated cells, an indication of forced mitotic exit. Importantly, in PTX-resistant cells, the combination therapy using SPION HT helps to overcome resistance by reducing the number of cells relative to the control. Conclusion: SPION HT potentiates PTX by significantly reducing cell survival, suggesting potential of combined treatment for future clinical translation. Keywords: iron oxide nanoparticles, chemotherapy, drug resistance, hyperthermia, taxanes